2015
DOI: 10.1155/2015/636548
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Retinal Peripapillary Segmentation in Early Alzheimer’s Disease Patients

Abstract: Decreased thickness of the retinal nerve fiber layer (RNFL) may reflect retinal neuronal-ganglion cell death. A decrease in the RNFL has been demonstrated in Alzheimer's disease (AD) in addition to aging by optical coherence tomography (OCT). Twenty-three mild-AD patients and 28 age-matched control subjects with mean Mini-Mental State Examination 23.3 and 28.2, respectively, with no ocular disease or systemic disorders affecting vision, were considered for study. OCT peripapillary and macular segmentation thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 61 publications
(81 reference statements)
1
61
0
2
Order By: Relevance
“…In other study, Gao et al [25] evaluated 25 patients with AD and found a significant reduction of macular volume in these patients. Salobrar-Garcia et al [50] also demonstrated a preferential reduction of macular parameters in mild-AD patients. In this study, the peripapilary RNFL thickness was thinner, but did not reach a significant difference compared with age-matched controls, suggesting a preferential involvement of the macula in early stages of the disease.…”
Section: Macular Thickness Measurements In Alzheimer’s Disease Patientsmentioning
confidence: 96%
“…In other study, Gao et al [25] evaluated 25 patients with AD and found a significant reduction of macular volume in these patients. Salobrar-Garcia et al [50] also demonstrated a preferential reduction of macular parameters in mild-AD patients. In this study, the peripapilary RNFL thickness was thinner, but did not reach a significant difference compared with age-matched controls, suggesting a preferential involvement of the macula in early stages of the disease.…”
Section: Macular Thickness Measurements In Alzheimer’s Disease Patientsmentioning
confidence: 96%
“…In addition, one study using SD-OCT showed a diffuse reduction of the RNFL and GCL combined in AD [49], although the authors were not able to determinate which layer was most affected by AD. Later studies have demonstrated IPL thinning in AD patients [41,50,52,56,57]. This reduction of ganglion cell complex thickness (GC-IPL and RNFL layers) in AD occurs to a larger extent than that accounted for age-related GC-IPL loss alone (about 0.3 μm/ year) [54].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…In addition, invivo studies have shown reduced macular thickness and volume in patients with AD [44,[48][49][50][51][52][53][54].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…With OCT, retinal changes are visualized both in ophthalmological disease and in neurodegenerative disease. Previous studies have shown that the retinal nerve fiber layer (RNFL) thickness and ganglion cell layer (GCL) thickness are reduced in subjects with multiple sclerosis (MS) [5], Parkinson disease (PD) [6], and AD [7–31].…”
Section: Introductionmentioning
confidence: 99%